Sock architecture : heels, toes & techniques for knitting awesome socks - Neel, Lara (Cooperative Press, 2014)
Sock Architecture is perfect for both experienced and novice sock knitters. This thorough, imaginative collection of sock shapes and patterns gives you the tools to construct an astounding variety of custom socks. All heels and toes are carefully explained and clearly photographed, and you can plug in your own numbers to work at the exact size and gauge you want. If you'd rather just pick up the needles and start knitting, Sock Architecture also includes 17 fully designed patterns. Most span five sizes, from women's extra small through men's large. And most of the patterns offer guidelines for an adjustable size so you can choose your own gauge, size, or both. Make socks that are as unique as you are!